Henry Rider Haggard in Zululand: A Reluctant Imperialist? - Marie-Claude BARBIER (E-REA)
This paper analyses Rider Haggard’s first major work, Cetywayo and his White Neighbours or Remarks on Recent Events in Zululand, Natal and the Transvaal, published in 1882, after six years in South Africa. Those years were crucial in the history of the country because of the two deadly conflicts fought by the British: the Anglo-Zulu War and the first Boer war, both marked by the traumatic defeats at Isandhlwana and Majuba Hill. On his return to England, Haggard decided to give an account of the events based on his own observations and perspective as an active witness. Though a supporter of British imperialism, Haggard criticized Britain’s political choices in Zululand at the time and tried to show that the principal cause of the conflicts was British ignorance of Zulu society. He blamed the arrival of Western civilisation for permanently compromising Zulu identity as its traders and missionaries brought with them evils which could no longer be eradicated. Torn between his admiration for the Zulu, which was to inspire him in his subsequent well-known works of fiction, and his belief that development of the colonies was essential for Britain, but also conscious that white domination was inescapable, he suggested a protectorate as being a lesser evil.